Pharmacoinformational, basic and clinical studies of 7-hydroxymatairesinol in the context of searching for effective and safe therapeutic approaches to the treatment of mastopathy - А. N. Rubashkina; I. Yu. Torshin; O. A. Gromova (Фармакокинетика и Фармакодинамика)
7-hydroxymatairesinol (7(OH)MR) is the main lignan of spruce extracts, characterized by oncoprotective and anti-inflammatory properties. The results of chemoreactome modeling made it possible to formulate the molecular mechanisms of the pharmacological effects of 7(OH)MR for anti-inflammatory (inhibition of 5-lipoxygenase, matrix metalloproteinase MMP2, mitogen-activated kinase p38-alpha, leukotriene b4 receptor, prostacyclin receptor), oncoprotective (antioxidant effect due to inhibition heme oxygenase-2, inhibition of cyclin-dependent kinases 3 and 4, epidermal growth factor, mTOR protein). An assessment of the transcriptomic effects of 7(OH)MR in breast cancer cells showed significant dose-dependent effects on the transcription of 3468 of 12700 genes. The 7(OH)MR molecule, reducing the expression of proliferative genes (401 genes) and chronic inflammation (148 genes), while simultaneously increasing the transcription of oncoprotective immunity genes (100 genes), inhibits the proliferation of tumor cells. Experiments on solid Ehrlich carcinoma showed a significant oncoprotective effect of 7(OH)MR at doses of 60, 120 mg/day, even while taking estrogen (p = 0.007). A clinical study showed that 7(OH)MR (60 mg/day, 1 month) helps normalize estrogen metabolism and improve the clinical symptoms of mastopathy.